Sickle cell disease in Saudi Arabia: the phenotype in adults with the Arab‐Indian haplotype is not benign. (13th November 2013) - Alsultan, Abdulrahman; Alabdulaali, Mohammed K.; Griffin, Paula J.; AlSuliman, Ahmed M.; Ghabbour, Hazem A.; Sebastiani, Paola; Albuali, Waleed H.; Al‐Ali, Amein K.; Chui, David H. K.; Steinberg, Martin H.
Summary Sickle cell disease (SCD) in Saudi patients from the Eastern Province is associated with the Arab‐Indian (AI) HBB (β‐globin gene) haplotype. The phenotype of AI SCD in children was described as benign and was attributed to their high fetal haemoglobin (HbF). We conducted a hospital‐based study to assess the pattern of SCD complications in adults. A total of 104 patients with average age of 27 years were enrolled. Ninety‐six per cent of these patients reported history of painful crisis; 47% had at least one episode of acute chest syndrome, however, only 15% had two or more episodes; symptomatic osteonecrosis was reported in 18%; priapism in 17%; overt stroke in 6%; none had leg ulcers. The majority of patients had persistent splenomegaly and 66% had gallstones. Half of the patients co‐inherited α‐thalassaemia and about one‐third had glucose‐6‐phosphate dehydrogenase deficiency. Higher HbF correlated with higher rate of splenic sequestration but not with other phenotypes. The phenotype of adult patients with AI SCD is not benign despite their relatively high HbF level. This is probably due to the continued decline in HbF level in adults and the heterocellular and variable distribution of HbF amongst F‐cells.